Unraveling what makes a monoclonal antibody difficult‐to‐express: From intracellular accumulation to incomplete folding and degradation via ERAD. Issue 1 (15th November 2019) - Mathias, Sven; Wippermann, Anna; Raab, Nadja; Zeh, Nikolas; Handrick, René; Gorr, Ingo; Schulz, Patrick; Fischer, Simon; Gamer, Martin; Otte, Kerstin
Abstract: Although most therapeutic monoclonal antibodies (mAbs) can routinely be produced in the multigram per litre range, some mAb candidates turn out to be difficult‐to‐express (DTE). In addition, the class of more complex biological formats is permanently increasing and mammalian expression systems like Chinese hamster ovary (CHO) cell lines can show low performance. Hence, there is an urgent need to identify any rate limiting processing step during cellular synthesis. Therefore, we assessed the intracellular location of the DTE antibody mAb2 by fluorescence and electron microscopy (EM) and revealed an accumulation of the antibody, which led to an aberrant morphology of the endoplasmic reticulum (ER). Analysis of underlying cellular mechanisms revealed that neither aggregation nor antibody assembly, but folding represented the reason for hampered secretion. We identified that the disulfide bridge formation within the antibody light chain (LC) was impaired due to less recognition by protein disulfide isomerase (PDI). As a consequence, the DTE molecule was degraded intracellularly by the ubiquitin proteasome system via ER‐associated degradation (ERAD). This study revealed that with the continuous emergence of DTE therapeutic protein candidates, special attention needs to be drawn to optimization processes to ensure manufacturability. Abstract :